2014
DOI: 10.2196/jmir.3003
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Patients Treated for Prostate Cancer: A Video Vignette Study With an Email-Based Educational Program in General Practice

Abstract: BackgroundMen who have been treated for prostate cancer in Australia can consult their general practitioner (GP) for advice about symptoms or side effects at any time following treatment. However, there is no evidence that such men are consistently advised by GPs and patients experience substantial unmet need for reassurance and advice.ObjectiveThe intent of the study was to evaluate a brief, email-based educational program for GPs to manage standardized patients presenting with symptoms or side effects months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
(28 reference statements)
2
20
0
Order By: Relevance
“…The only study not to report positive behaviour change found that the intervention designed to improve general practitioners’ management of prostate cancer treatment side‐effects did not promote management plans consistent with expert opinion. The participants reported that they were reluctant to engage with the learning content because they did not consider the case study answers reflected best practice, leading the authors to suggest that greater involvement of end users in case study development was required, especially when the evidence was inconclusive …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The only study not to report positive behaviour change found that the intervention designed to improve general practitioners’ management of prostate cancer treatment side‐effects did not promote management plans consistent with expert opinion. The participants reported that they were reluctant to engage with the learning content because they did not consider the case study answers reflected best practice, leading the authors to suggest that greater involvement of end users in case study development was required, especially when the evidence was inconclusive …”
Section: Resultsmentioning
confidence: 99%
“…Five randomised controlled trials (RCTs) generated the highest level of evidence (level II). Lower levels of evidence emerged from: five pre–post‐test studies, two prospective cohort studies, two quasi experimental studies, one mixed‐methods study, one time series analysis and one standardised patient study …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations